Effect of Quinoa (Chenopodium quinoa Willd.) Starch and Seeds on the Physicochemical and Textural and Sensory Properties of Chicken Meatballs during Frozen Storage - Jin-Hwa Park; Yun-Jin Lee; Jeong-Gyu Lim; Ji-Hye Jeon; Ki-Sun Yoon (Foods, 2021)
The effects of starch (corn and quinoa) and quinoa seeds on chicken meatballs’ physicochemical, textural, and sensory properties were investigated during frozen storage. The chicken meatballs were prepared with corn starch (CS), quinoa starch (QS), quinoa seeds (Q), and combinations of corn starch and quinoa seeds (CS-Q), and quinoa starch and quinoa seeds (QS-Q), which were subjected to five freeze–thaw (F-T) cycles of temperature fluctuation conditions during frozen storage. Regardless of the type used (CS or QS), adding starch resulted in fewer cooking, drip, and reheating losses in chicken meatballs during frozen storage. The values of the hardness, gumminess, and chewiness of chicken meatballs with CS or QS were half those of chicken meatballs without starch, indicating that the addition of starch inhibited the change in the meatballs’ texture. The total volatile basic nitrogen (TVB-N) and thiobarbituric acid reactive substance (TBARS) values were progressive but did not dynamically increase during five F-T cycles. Chicken meatballs containing CS-Q or QS-Q showed significantly lower TBARS values than those with CS, QS, or Q after five F-T cycles. Adding quinoa seeds significantly increased the antioxidant activity and the chewiness of meatballs (p < 0.05) compared with starch only. The addition of the combination of QS-Q to chicken meatballs increased the values of taste, texture, and overall acceptability, indicating that quinoa starch and seeds may be introduced as premium ingredients to frozen meat products.